Optimizing Investment Strategies with the Reconfigurable Hardware Platform RIVYERA - Christoph Starke; Vasco Grossmann; Lars Wienbrandt; Sven Koschnicke; John Carstens; Manfred Schimmler (International Journal of Reconfigurable Computing)
The hardware structure of a processing element used for optimization of an investment strategy for financial markets is presented. It is shown how this processing element can be multiply implemented on the massively parallel FPGA-machine RIVYERA. This leads to a speedup of a factor of about 17,000 in comparison to one single high-performance PC, while saving more than 99% of the consumed energy. Furthermore, it is shown for a special security and different time periods that the optimized investment strategy delivers an outperformance between 2 and 14 percent in relation to a buy and hold strategy.